Physical activity and ischaemic heart disease in middle-aged British men. - Shaper, A G (1991)
OBJECTIVE--To assess the relation between reported physical activity and the risk of heart attacks in middle aged British men. DESIGN--Prospective study of middle-aged men followed for a period of eight years (The British Regional Heart Study). SETTING--One general practice in each of 24 British towns. PARTICIPANTS--7735 men aged 40-59 years at initial examination. END POINT--Heart attacks (non-fatal and fatal). MEASUREMENTS AND MAIN RESULTS--During the follow up period of eight years 488 men suffered at least one major heart attack. A physical activity score used was developed and validated against heart rate and lung function (FEV1) in men without evidence of ischaemic heart disease. Risk of heart attack decreased significantly with increasing physical activity; the groups reporting moderate and moderately vigorous activity experienced less than half the rate seen in inactive men. The benefits of physical activity were seen most consistently in men without preexisting ischaemic heart disease and up to levels of moderately vigorous activity. Vigorously active men had higher rates of heart attack than men with moderate or moderately vigorous activity. The relation between physical activity and the risk of heart attack seemed to be independent of other cardiovascular risk factors. Men with symptomatic ischaemic heart disease showed a reduction in the rate of heart attack at light or moderate levels of physical activity, beyond which the risk of heart attack increased. Men with asymptomatic ischaemic heart disease showed an increasing risk of heart attack with increasing levels of physical activity, but with a progressive decrease in case fatality. Overall, men who engaged in vigorous (sporting) activity of any frequency had significantly lower rates of heart attack than men who reported no sporting activity. However, when all men reporting regular sporting activity at least once a month were excluded from analysis, there remained a strong inverse relation between physical activity and the risk of heart attack in men without pre-existing ischaemic heart disease. CONCLUSION--This study suggests that the overall level of physical activity is an important independent protective factor in ischaemic heart disease and that vigorous (sporting) exercise, although beneficial in its own right, is not essential in order to obtain such an effect.